Gender difference in the skeletal muscle ageing and regulation of myosin heavy chain expression by TIS21 gene in the C57BL/6J mice - KHATUN MST RESHMA (The Graduate School, Ajou University, 2019)
There are evidences TIS21/BTG2/PC3, an antiproliferative gene, is essential for multiple biological functions such as cell proliferation, growth, differentiation, senescence and cell death. However, no study has been found that examined its role in muscle function and maintenance. In this study, we investigated whether TIS21 has any role in the regulation of muscle protein, myosin heavy chain (MyHCs), expression in gastrocnemius (GA) skeletal muscle of male and female mice along with their ageing process. Firstly, we measured specific changes of GA muscle and body weight and their ratio at different age of C57BL/6J male and female mice. The absolute muscle and body weight were significantly higher in the TIS21-knock out (KO) young (12 wk) and mid-old (38 wk) male mice as compared with TIS21-wild type (WT). However, there was no significant change in the muscle and body weight and their ratio between the TIS21 WT and TIS21 KO female mice. Secondly, our immunoblot data revealed that KO of TIS21 gene results significant reduction of MyHCs protein expression in GA of mid-old (34 wk-38 wk) female mice. The reduction was also significant in the old female mice (19 months). However, TIS21 KO male mice did not show that kind of significant decline in MyHCs protein expression compared to its WT in ageing response. Furthermore, analysis of mRNA expression by Real-time PCR showed that the transcription of MyHC2a and MyHC2b (type II fiber isoforms) significantly downregulated in the old TIS21 KO-female mice (19 months) rather than old male mice (24 months) compared to its WT. Finally, transient transfection including TIS21 overexpression into C2C12 cells following luciferase assay demonstrates that TIS21 might regulate the expression of MyHCs from their promoter level. Overall, our data implicate a potential role of TIS21 in MyHCs expression, where TIS21 controls the transcriptional level in female mice. Keywords: Skeletal Muscle, Myosin heavy chain, TIS21 and Ageing.
학위논문(석사)--아주대학교 일반대학원 :의생명과학과,2019. 2